2000
DOI: 10.1152/jn.2000.83.2.888
|View full text |Cite
|
Sign up to set email alerts
|

Sacrocaudal Afferents Induce Rhythmic Efferent Bursting in Isolated Spinal Cords of Neonatal Rats

Abstract: The ability of mammalian spinal cords to generate rhythmic motor behavior in nonlimb moving segments was examined in isolated spinal cords of neonatal rats. Stimulation of sacrocaudal afferents (SCA) induced alternating left-right bursts in lumbosacral efferents and in tail muscles. On each side of the tail, flexors, extensors, and abductors were coactive during each cycle of activity. This rhythm originated mainly in the sacrocaudal region because it persisted in sacrocaudal segments after surgical removal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 31 publications
4
53
0
1
Order By: Relevance
“…5B). This EMG activity is reminiscent of the rhythmic activity evoked in the neonatal rat tail in vitro by afferent stimulation (Lev-Tov et al 2000). In Fig.…”
Section: Cutaneous Stimulation In Chronic Spinal Ratsmentioning
confidence: 67%
“…5B). This EMG activity is reminiscent of the rhythmic activity evoked in the neonatal rat tail in vitro by afferent stimulation (Lev-Tov et al 2000). In Fig.…”
Section: Cutaneous Stimulation In Chronic Spinal Ratsmentioning
confidence: 67%
“…The ability of input from load and joint receptors to retrain the locomotor CPGs and improve motor function in humans with SCI (Dietz et al, 1997;Dietz, 2009;Edgerton et al, 2006;2008;Wernig et al, 1998) raises questions about the functional organization of the mediating pathways and the possibility of other sensory modalities to reactivate the CPGs. Our finding that stimulation of nociceptive and nonnociceptive sacrocaudal afferents (SCAs) has an extraordinary capacity to activate the CPGs in isolated spinal cords of neonatal rats (Lev-Tov et al, 2000;Strauss and Lev-Tov, 2003;Blivis et al, 2007; also see Klein and Tresch, 2010;for rat;and Mandadi and Whelan, 2009; for mouse) provided us not only with an additional potent means for activating the CPGs, but also with an experimentally accessible model to study the neuronal circuitry linking the SCA and CPGs and their mechanism of action. Using this model, we showed that activation of the CPGs by SCA stimulation required glutamatergic synaptic excitation (Strauss and Lev-Tov, 2003) of heterogeneous groups of sacral neurons with crossed and uncrossed ascending projections through the ventral (VF) and lateral white matter funiculi (Etlin et al, 2010;Lev-Tov et al, 2010).…”
Section: Introductionmentioning
confidence: 86%
“…Spinal cords (T6-Co3) were isolated from P1-P3 isoflurane-anesthetized male or female rats (Lev-Tov and Delvolvé, 2000;Lev-Tov et al, 2000;Delvolvé et al, 2001;Blivis et al, 2007). Preparations were transferred to a recording chamber and superfused continuously with an oxygenated artificial CSF (Kremer and Lev-Tov, 1997;Lev-Tov et al, 2000;Delvolvé et al, 2001;Blivis et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that cauda equina stimulation can effectively activate thoracosacral CPGs (Lev-Tov et al 2000;Whelan et al 2000). Because it offers a complementary method to activate thoracosacral CPGs, we examined whether afferent stimulation could evoke coordinated bursting from cervical segments.…”
Section: Cauda Equina Stimulation Can Evoke Coordinated Rhythmic Actimentioning
confidence: 99%